Аtherosclerosis‐like changes in the rabbit aortic wall induced by immunization with native high‐density lipoproteins. Issue 4 (13th August 2020) - Fomina, Kseniya; Beduleva, Liubov; Menshikov, Igor; Zerjawi, Abdulkadhim; Terentiev, Alexey; Sidorov, Alexandr; Khramova, Tatyana; Abisheva, Nadezhda; Gorbushina, Anna
Abstract: Introduction: A high level of total cholesterol or low‐density lipoprotein (LDL) cholesterol is considered the main cause of atherosclerosis and cardiovascular disease. For this reason, experimental atherosclerosis is induced by creating high blood cholesterol in animals. However, the hypothesis that atherosclerotic processes are mostly caused by immune (autoimmune) mechanisms has recently been gaining traction. At the same time, no experimental model has been developed that clearly demonstrates the autoimmune mechanism by which atherosclerosis develops and reproduces the full picture of atherosclerosis solely by means of an immune response, without resorting to additional interventions such as a high‐cholesterol diet or the use of genetic models of hyperlipidemia. Previously, we were able to induce atherosclerosis‐like lesions in the aorta and the development of pericardial fat in rats by immunizing them with human native lipoproteins. The purpose of this study was to test whether atherosclerosis can be induced in normocholesterolaemic rabbits by immunizing them with human native high‐density lipoproteins (hnHDL). Methods: Rabbits were immunized with hnHDL. Aortic wall structure, plasma cholesterol level, and antibodies against HDL were studied. Results: Immunization with hnHDL was found to cause atherosclerosis‐like lesions in the rabbit aorta such as adipocytic and chondrocytic metaplasia, proteoglycan deposits, leukocytic infiltration. Atherosclerosis‐like lesions developed in the aorta of hnHDL‐immunized rabbits against a background of normal blood LDL‐cholesterol level. Therefore, a high plasma cholesterol level is not the sole cause of atherosclerosis. The immune response against HDL is an independent cause of atherogenesis. Conclusions: A rabbit model of atherosclerosis caused by immunization with hnHDL can be widely used to examine the mechanisms occurring during atherogenesis. Abstract : Immunization with human native high‐density lipoproteins (hnHDLs) induces atherosclerosis‐like lesions in the rabbit aorta such as adipocytic and chondrocytic metaplasia, proteoglycan deposits, and leukocytic infiltration. Atherosclerosis‐like lesions develop in the aorta of hnHDL‐immunized rabbits against a background of normal blood low‐density lipoprotein‐cholesterol level. Consequently, the immune response against HDL may be an independent cause of atherogenesis, and HDL is the potential target of the immune attack that leads to atherosclerosis.